Copper oxide modification to improve the photocatalytic activity of titanium dioxide nanoparticles: P25 versus P90. Issue 1 (July 2020) - Yuliati, L; Hasan, N; Lintang, H O
Abstract: Titanium dioxide (TiO2 ) has been recognized as one of the most active photocatalysts for organic pollutant degradation under ultraviolet (UV) light irradiation. In order to reduce the fast charge recombination in the TiO2, various methods have been investigated, including the addition of metal oxide co-catalysts. Owing to the characteristic of the nanoparticles, the modification of nanoparticles involving heat treatment is still a challenging task. In this work, two commercial TiO2 nanoparticles, namely P25 and P90 (Evonik), were modified by copper oxides (CuO) and the photocatalytic activity was evaluated for degradation of 2, 4-dichlorophenoxyacetic acid (2, 4-D) under UV light. The CuO/P25 and CuO/P90 samples with various loading amounts (0.1, 0.25, 0.5 and 1.0 wt %) were prepared by precipitation of copper(II) nitrate to the P25 or P90 nanoparticles at pH of 9, followed by calcination at 573 K. X-ray diffraction (XRD) patterns indicated that all samples have the characteristics of both anatase and rutile phases. While the addition of CuO did not much affect the structure, crystallite size, and anatase-rutile ratio of the P25 and P90 nanoparticles, the presence of the copper species was confirmed by the scanning electron microscopy (SEM) equipped with the energy-dispersive X-ray (EDX) spectroscopy. Moreover, fluorescence spectra also showed that the CuO quenched the emission intensity of both the P25 and P90 nanoparticles, suggesting the successful decrease of the charge recombination in the TiO2 nanoparticles. Photocatalytic activity tests showed that the P25 and P90 gave percentage degradation of 90 and 47 %, respectively, after a 1-hour reaction. Even though not much improvement was observed for P25 TiO2 nanoparticle after the CuO addition (92 %), the activity of P90 nanoparticle was enhanced from 47 % to 86–87 % with the CuO addition of 0.1–0.25 wt %. This study demonstrated that it is feasible to improve the photocatalytic activity of TiO2 commercial nanoparticles, in this case, the P90, by surface modification using the CuO.